2007
DOI: 10.1086/511644
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Pseudomonas aeruginosa Infection Caused by Contaminated Mouth Swabs

Abstract: Contamination of mouth swabs during production caused the largest-ever outbreak of P. aeruginosa infection in Norway. Susceptible patient groups should use only documented quality-controlled, high-level-disinfected products and items in the oropharynx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 109 publications
(168 reference statements)
0
48
0
4
Order By: Relevance
“…1,3,6,13,14,17,19,20 Hemodialysis was one of the factors that was associated with the outcome in univariate analysis in the present study but was not kept in the final model. temporal, spatial and clinical associations between this variable and the dependent variable (infection or colonization by MR-PA strain during hospitalization) were observed during the study.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…1,3,6,13,14,17,19,20 Hemodialysis was one of the factors that was associated with the outcome in univariate analysis in the present study but was not kept in the final model. temporal, spatial and clinical associations between this variable and the dependent variable (infection or colonization by MR-PA strain during hospitalization) were observed during the study.…”
Section: Discussionmentioning
confidence: 77%
“…1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Among immunocompromised patients with human immunodeficiency virus (HIV) infection or AIDS, few studies have shown prior hospitalization, antimicrobial use, and CD4 cell count below 50/mm 3 as risk factors for P. aeruginosa infection. [21][22][23] none of these HIV/AIDS studies assessed the risk factors for acquisition of MR-PA strains.…”
Section: Introductionmentioning
confidence: 99%
“…P. aeruginosa has also been linked to infectious outbreaks from contaminated medical devices. This is mainly due to the organism's ability to effectively produce a biofilm that allows adherence to plastic materials and catheters and helps prevent destruction by antibiotics [24][25][26] . This property, along with increasing broad-spectrum antibiotic use, especially in critical care settings, has led to an increase in MDR strains across the USA and the world [2] .…”
Section: Quinolone Resistancementioning
confidence: 99%
“…Pseudomonas aeruginosa is a Gram-negative bacterium that is well known to be involved in a large number of human infections (14,30). Numerous outbreaks have been linked directly to its presence on medical equipment (11,15,16,25). The persistence of this bacterium in the environment can be attributed to its ability to form biofilms that increase its resistance to disinfection treatments.…”
mentioning
confidence: 99%